DEM simulation of bionic subsoilers (tillage depth >40 cm) with drag reduction and lower soil disturbance characteristics. (May 2018) - Sun, Jiyu; Wang, Yueming; Ma, Yunhai; Tong, Jin; Zhang, Zhijun
Highlights: Bionic structure of subsoiler learn from shark skin had more influence on the resistance and energy consumption than the ordinary subsoiler. DEM result showed that the bionic structures in both shank and tine with height-to-lateral-rib-spacing ratio of 0.57 had a better effect. The soil bottom disturbance and the soil overall performance were used to demonstrate the performance of the subsoiler. Abstract: Successive years of mechanical operations and conservation tillage in Northeast China have made subsoiling necessary, and the tillage depth can be no less than 40 cm. In this paper, a bionic design method was used to reduce subsoiler energy consumption and soil disturbance. The bionic structural elements, i.e., triangular prism (BTP) and partial circular column (BPCC), were inspired by the placoid scale rib structure of shark skin, which has low drag. These elements were then applied to the subsoiler to reduce energy consumption. Six types of bionic subsoilers were designed. Discrete element modeling (DEM) was used to simulate and analyze the interactions of the bionic subsoilers and an ordinary subsoiler (O-S) with the soil. The results showed that bionic subsoilers with a shank and BTP in the horizontal direction of motion (S-T-H) and tines with the BTP parallel to the centerline (T-T) had lower draft requirements and energy consumption than the other designs. The draft requirements and energy consumption of S-T-H subsoilers with different height-to-lateral-rib-spacing ( h / s ) ratios were then compared. The subsoiler with a bionic element h / s of 0.57 (S-T-H-0.57) had a lower draft requirement (1292.59 N) and a lower total energy requirement (23.48 J) than the other designs. A soil disturbance analysis demonstrated that S-T-H-0.57-T-T (bionic elements arranged in both the shank and tine) provided superior benefits in terms of root growth and improved crop stress resistance. The result is consistent with the mechanical analysis of the riblet, which will be helpful for designing new subsoilers with reduced drag and soil disturbance.